Prevalence of Microsporidium and Other Intestinal Parasites in Children from Malatya, Turkey - Calik, Sinan; Karaman, Ulku; Colak, Cemil (Springer, 2011)
Parasite infections are common during the critical developmental period in children. The occurrences of intestinal parasites are also common in orphanage, nurseries and schools in Turkey. The study was carried out to determine the percentage of microsporidium and intestinal parasites in children from Malatya, Turkey. This study was carried out at the Department of Parasitology of Inonu University, Turgut Ozal Medical Center, during January-December 2006. Totally, 1,181 stool samples were examined using the native-Lugol, sedimentation-techniques, modified trichrome (MTS), acid-fast-trichrome stain and calcofluor staining methods. In addition, perianal region material was taken from the children to examine with cellophane tape method. Power analyses were performed for statistical analyses used. Microsporidia were found in 92 (7.8%) of the samples, and also intestinal parasites were detected in 329 (27.8%). The numbers of infections according to the species were as follows: 69 (5.8%) Entamoeba coli, 7 (0.6%) Blastocystis hominis, 114 (9.7%) Giardia intestinalis, 15 (1.3%) Iodomoeba butchlii, 8 (0.7%) Dientamoeba fragilis, 7 (0.6%) Taenia spp. 70 (5.9%) Enterobius vermicularis, 11 (0.9%) Hymenolepis nana, 25 (2.1%) Trichomonas intestinalis, 1 (0.1%) Ascaris lumbricoides and 2 (0.2%) Chilomastix mesnilii. Also, greater than 90% power values were achieved for statistical analyses. Whereas the detection rates of microsporidium and intestinal parasites were found to be low, it was concluded that in addition to intestinal parasites, microsporidium should be also searched for in children with complaints of intestinal system.
Keywords: Children; Microsporidia; Intestinal parasites